1982
DOI: 10.1055/s-0038-1657261
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Deep Venous Thrombosis in Patients with an Acute Myocardial Infarction Treated with Acenocoumarol or Indobufen

Abstract: SummaryIn a randomized double blind clinical trial, we compared indobufen, an antiplatelet drug, with acenocoumarol for the prevention of deep venous thrombosis (D. V. T.) in patients with acute myocardial infarction. Therapy was started on admission and continued for 10 days. All patients were screened daily with impedance plethysmography (I.P.G.) and 125I-fibrinogen leg scanning. Diagnosis of D.V.T. was made when either one or both tests became positive. 74 patients were randomized to treatment with indobufe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Several clinical researchers have documented that the drug is active as an antiplatelet agent at a dose of 200-400 mg/day and has a good tolerability also during prolonged treatments (6,8). The drug has been shown to possess antithrombotic activity in a variety of experimental models (6,9) as well as in human studies (10,11). Indobufen exists in two forms that are optical isomers.…”
mentioning
confidence: 99%
“…Several clinical researchers have documented that the drug is active as an antiplatelet agent at a dose of 200-400 mg/day and has a good tolerability also during prolonged treatments (6,8). The drug has been shown to possess antithrombotic activity in a variety of experimental models (6,9) as well as in human studies (10,11). Indobufen exists in two forms that are optical isomers.…”
mentioning
confidence: 99%
“…We found that six additional trials on interventions that are generally not used anymore in daily practice (platelet inhibitors, heparinoids, and coumarins) increased statistical inconsistency without contributing significant information to the network. 63 64 65 66 67 68 Therefore we excluded these trials from the main analysis. We also excluded two randomised controlled trials from the venous thromboembolism outcome analysis (but not from the other outcomes) because of unusually high pulmonary embolism rates.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we noted evidence of inconsistency in the node-splitting models of the venous thromboembolism and bleeding outcome. We found that six additional trials on interventions that are generally not used anymore in daily practice (platelet inhibitors, heparinoids, and coumarins) increased statistical inconsistency without contributing significant information to the network 636465666768. Therefore we excluded these trials from the main analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical researches have documented that the drug is active as an antiplatelet agent in vivo at a dose of 200-400 mg/day and has a good tolerability also during prolonged treatment (7)(8)(9). The drug has been shown to possess antithrombotic activity in a variety of experimental models (7,10) as well as in human studies (11)(12)(13). Due to the anti-cyclooxygenase mechanism of action, most side-effects of indobufen -like aspirin most frequently gastric -are assumed to be related to a block of cyclooxygenase activity in cells other than platelets.…”
Section: Introductionmentioning
confidence: 99%